'War and Peace' at the 1980 Moscow and 2014 Sochi Olympics: The Role of Hard and Soft Power in Russian Identity. Issue 14 (22nd September 2018) - Kramareva, Nina; Grix, Jonathan
Abstract: Russia's (and the USSR's) use of sports mega-events (SMEs) makes this BRICS country (Brazil, Russia, India, China, and South Africa) not only an outlier among emerging states, but also among key SME hosts generally. Both the historic Moscow Olympics (1980) and the more recent hosting of the 2014 Sochi Winter Olympics provide evidence that Russia has, on both occasions, focussed on geopolitical priorities using hard power (military might) at the expense of soft power acquisition. Furthermore, both Olympics were, first and foremost, used to pursue domestic soft power goals. This, again, makes Russia an outlier in terms of the political use of SMEs by states in the literature on this subject. The 1980 Olympic Games, therefore, in terms of their potential to generate soft power and national unity, turned out to be a mis-used opportunity for Russia. To what extent is this specific to Russia and could the first Russian Olympics provide valuable insight into the modern-day hosting of SMEs by Russia (2014/2018)?